Beasts, humans, and transhumans in the Middle Ages and the Renaissance - Clay, J. Eugene (Brepols, 2020)
From shape-shifting Merlin to the homunculi of Paracelsus, the nine essays of this collection explore the contested boundaries between human and non-human animals, between the body and the spirit, and between the demonic and the divine. Drawing on recent work in animal studies, posthumanism, and transhumanism, these innovative articles show how contemporary debates about the nature and future of humanity have deep roots in the myths, literature, philosophy, and art of the Middle Ages and the Renaissance. The authors of these essays demonstrate how classical stories of monsters and metamorphoses offered philsophers, artists, and poets a rich source for reflection on marriage, resurrection, and the passions of love. The ambiguous and shifting distinctions between human, animal, demon, and angel have long been contentious. Beasts can elevate humanity: for Renaissance courtiers, horsemanship defined nobility. But animals are also associated with the demonic, and medieval illuminators portrayed Satan with bestial features. Divided into three sections that examine metamorphoses, human-animal relations, and the demonic and monstrous, this volume raises intriguing questions about the ways humans have understood their kinship with animals, nature, and the supernatural.
Keywords: Geschichte 500-1700; Mischwesen; Bildliche Darstellung; Tiere; Fiktionale Darstellung; Mensch; Konferenzschrift -- 2013 -- Phoenix, Ariz.